Ability of Shirasu‐based Material for Adsorption of Metal Ions and Its Promotion for Catalytic Decomposition of Nitrous Oxide. Issue 46 (8th December 2022) - Umegaki, Tetsuo; Noguchi, Daisuke; Fukumoto, Tsubasa
Abstract: This work investigated ability of Shirasu‐based material for adsorption of metal ions and their promotion effect for catalytic decomposition of nitrous oxide. Catalytically active cobalt and copper species were adsorbed on the Shirasu‐based material by immerse process of aqueous matal solutions. In all the Co/Cu ratios (Co/(Co+Cu)=1, 0.75, and 0.5), cobalt species were preferentially adsorbed on the Shirasu‐based material. The cobalt species tended to be adsorbed on the silica sites of the sample with Co/(Co+Cu)=0.75. and the catalyst exhibited the highest activity for decomposition of nitrous oxide. Introduced nitrous oxide was completely decomposed at the reaction temperatures above 673 K. Abstract : Ability of a shirasu‐based material for adsorption of metal ions and its promotion for catalytic decomposition of nitrous oxide were investigated in the present study. Cobalt species preferentially adsorbed on a shirasu ballon, and binary Co, Cu‐supported catalysts showed high and durable activity for N2 O decomposition.